2020
DOI: 10.1039/d0ra06640k
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of expensive Pt/C catalysts from the end-of-life membrane electrode assembly of proton exchange membrane fuel cells

Abstract: A sustainable approach for the recovery of EoL MEAs and possibility of pushing the recovered products back into the supply chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, chemical methods can achieve the stratification of MEA. In past studies, it has been reported that soaking the MEA in an aqueous alcohol solution or using a 50% isopropanol (IPA) solution resulted in complete delamination of the MEA [26], and that using dilute sulfuric acid as a pretreatment reagent obtained good results [26,27]. In this study, the use of 50% IPA effectively separate PEM, GDL, and CL which undergo solid-liquid separation for subsequent Pt leaching.…”
Section: Introductionmentioning
confidence: 82%
“…However, chemical methods can achieve the stratification of MEA. In past studies, it has been reported that soaking the MEA in an aqueous alcohol solution or using a 50% isopropanol (IPA) solution resulted in complete delamination of the MEA [26], and that using dilute sulfuric acid as a pretreatment reagent obtained good results [26,27]. In this study, the use of 50% IPA effectively separate PEM, GDL, and CL which undergo solid-liquid separation for subsequent Pt leaching.…”
Section: Introductionmentioning
confidence: 82%
“…1 However, the high cost of FCVs ascribed to the expensive perfluorinated proton exchange membranes (such as Gore Select) and the platinum catalyst seems to hinder their widespread dissemination. 2 In contrast, anion exchange membrane fuel cells (AEMFCs) have been manifested as a promising alternative to PEMFCs owing to the deployment of less-expensive AEMs and non-PGM catalysts. 3 AEMs play a pivotal role in AEMFCs and other alkaline electrochemical devices not only as a gas separator and ion transporter but also as an electrode binder in the catalyst layer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent advancement in proton exchange membrane fuel cells (PEMFCs) have promoted their applications, in particular, for fuel cell vehicles (FCVs), thanks to their zero-emission, rapid, and long-range running for a single fueling . However, the high cost of FCVs ascribed to the expensive perfluorinated proton exchange membranes (such as Gore Select) and the platinum catalyst seems to hinder their widespread dissemination . In contrast, anion exchange membrane fuel cells (AEMFCs) have been manifested as a promising alternative to PEMFCs owing to the deployment of less-expensive AEMs and non-PGM catalysts …”
Section: Introductionmentioning
confidence: 99%